Common Pillars Between the Surrealist Graphic Art (‎Printmaking) and Architecture During the Twentieth Century - حاجوج, اليسار (Latakia University Journal -Engineering Sciences Series, 2021)
The twentieth century embraced pivotal changes and qualitative leaps in the various fields of human life. This century has witnessed effervescence climaxes in the arts in general and an acceleration in the movement of schools and artistic trends of all genres. Then, the surrealist mentality came to leave its echoes as a modern artistic trend in the produces of arts such as poetry, literature, theatre, music, plastic arts, architecture and others, after its extensions were monitored in the arts of ancient man. Among all influence of the arts on each other were the deep intersections between surrealist graphic art (‎Printmaking) on the one hand, and surrealist architecture on the other; as these two arts like the rest of the visual arts are subject to the evaluation standards of the same visual arts. And they share basic features based on the peculiarity of the design elements in them and their ability to dive into the world of surrealism despite the association of architecture with the utilitarian function.